My Favorite Case to Teach: A Literal “Gateway” for Students to Learn Contract Formation, Contract Terms, and Legal Realism - Daniel Keating (Washington University Journal of Law & Policy, 2017)
This Essay explains the continued relevance of the issues discussed in Hill v. Gateway 2000, Inc. twenty years later. Keating describes his approach to teaching the case in his classroom, highlighting the broad and narrow issues under Article 2 of the Uniform Commercial Code implicated by the underlying facts. Keating disagrees with the outcome of the case, but praises its value as a teaching tool for sales contract formation and broader policy issues in the legal system.
Keywords: Hill v. Gateway 2000; Inc.; Article 2; contract terms; legal realism; Uniform Commercial Code; UCC; sales contract formation; legal system; Gateway 2000; Judge Frank Easterbrook